Flame ionization testing in an internal combustion engine to measure the speed of the flame for gaseous fuels - K., Mohanesen; D., Ramasamy; K., Kadirgama; M. M., Noor; M. M., Rahman (IOP Publishing, 2019)
The study was carried for combustion ionization flame testing on a K3-VE engine cylinder head. The main purpose of this experiment is to measure the speed of flame by using multiple ionization (ION) probe systems. The main purpose is to determine the feedback from the probe for engine control systems. The fuel that use in this experiment is LPG, because LPG gas causes a lot misfire during combustion due to its gaseous state. The testing probe was installed inside the engine combustion chamber with specific distance with a design fitment for the ION Probe. When the fuel is supplied in to the engine and the spark plug light up the fuel, it produces a flame which is ionised, at the same time, when this flame touches the probe, it will generate a signal. The probe is connected to a circuit, when the signal is generated by the flame, the circuit will process the signal. A user interface was created to display the result of the experiment. Also, a camera was used to catch the flame to validate with the result. By using calculation, the speed of the flame can be determined to 20.60 m/s. The signal of the flame can be further used to improve the efficiency of the engine by adding a chip to the circuit to convert the signal and send to the vehicle ECU to control the ignition time for better engine performance.